Optimizing Employee Performance Through Job Satisfaction - Desyanyo Gultom, Romulus; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Human resources (HR) are closely related to aspects of employee employment and organizational management. The phenomenon that occurs at BPJS Employment Pematang Siantar and Kisaran Branch Offices is that the lack of employee discipline in work and time makes employee performance less good. This is because employees feel dissatisfied with their work because there is no organization that pays attention to employees and there is no compensation so that employee performance decreases. The results of this research are as follows: Work Discipline has a positive and significant effect on Job Satisfaction with an original value of 0.858 and ap value or sig of 0.000. Work Discipline has a positive and significant effect on Employee Performance with an original value of 0.174 and ap value or sig of 0.006. Job Satisfaction has a positive and significant effect on Employee Performance with an original value of 0.770 and ap value or sig of 0.000. Work Discipline influences employee performance indirectly through Job Satisfaction with an original value of 0.661 and ap value or sig of 0.000.